Preventing Violence Against Women and Children in Mandailing Natal Regency: A Criminological Perspective - Zul Fahmi (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2025)
ABSTRACT ENGLISHThis study analyzes the patterns and characteristics of violence against women and children in Mandailing Natal Regency during 2023–2024, focusing on sexual violence, domestic abuse, and homicide. The primary aggravating factors include poverty, gender inequality, early marriage, low educational attainment, and weak law enforcement. A criminological approach, drawing on Social Disorganization, Strain, Social Control, and Labeling theories, was employed to uncover root causes and propose prevention strategies based on economic empowerment, education, and legal reform. A qualitative methodology, utilizing literature review and content analysis, was applied to assess key themes in primary and secondary data sources, including books, scholarly articles, and local and national news reports. The findings reveal that sexual violence constitutes the most prevalent category, followed by domestic abuse often resulting in fatalities, and a rising incidence of child sexual exploitation, predominantly perpetrated by acquaintances of the victims. Factors such as gender disparity, poverty, limited educational opportunities, and inadequate law enforcement significantly exacerbate these conditions. Effective mitigation requires synergy among government agencies, community stakeholders, and related sectors, including strengthening legal frameworks, enhancing law enforcement capacities, and providing integrated support services. Community-based interventions and sustained educational programs, engaging religious and customary leaders—are expected to foster a safer, more inclusive environment. Cross-sector collaboration is identified as the key to reducing violence and bolstering public confidence in the justice system. ABSTRACT INDONESIANPenelitian ini menganalisis pola dan karakteristik kekerasan terhadap perempuan dan anak di Kabupaten Mandailing Natal pada periode 2023-2024, dengan fokus pada kekerasan seksual, penganiayaan domestik, dan pembunuhan. Faktor utama yang memperburuk situasi ini adalah kemiskinan, ketimpangan gender, pernikahan dini, rendahnya tingkat pendidikan, dan lemahnya penegakan hukum. Pendekatan kriminologi, dengan menggunakan teori Disorganisasi Sosial, Strain, Social Control, dan Labeling, diterapkan untuk menggali akar permasalahan dan menawarkan solusi pencegahan berbasis pemberdayaan ekonomi, pendidikan, serta reformasi hukum. Metode kualitatif dengan pendekatan studi literatur dan analisis konten digunakan untuk menilai tema-tema utama dalam data primer dan sekunder, termasuk buku dan artikel jurnal, serta laporan berita local dan nasional. Hasil penelitian menunjukkan bahwa kekerasan seksual adalah kasus dominan, diikuti oleh penganiayaan domestik yang sering berujung pada kematian, serta meningkatnya eksploitasi seksual terhadap anak, terutama oleh pelaku yang dikenal korban. Faktor-faktor seperti ketimpangan gender, kemiskinan, rendahnya pendidikan, dan lemahnya penegakan hukum berperan besar dalam memperburuk kondisi ini. Penanggulangan kekerasan memerlukan sinergi antara pemerintah, masyarakat, dan sektor terkait, termasuk penguatan regulasi, peningkatan kapasitas aparat penegak hukum, serta penyediaan layanan terintegrasi. Pendekatan berbasis komunitas dan edukasi berkelanjutan diharapkan dapat menciptakan lingkungan yang lebih aman dan inklusif, dengan melibatkan tokoh agama dan adat. Kolaborasi lintas sektor menjadi kunci dalam mengurangi kekerasan dan meningkatkan kepercayaan terhadap sistem hukum.